H2O2/O2 self-supply and Ca2+ overloading MOF-based nanoplatform for cascade-amplified chemodynamic and photodynamic therapy - Liang, Yujia; Cai, Zhengmin; Tang, Yamei; Su, Chenglin; Xie, Liye; Li, Yan; Liang, Xinqiang (Frontiers in Bioengineering and Biotechnology, 2023)
Reactive oxygen species (ROS)-mediated therapies have been usually considered as noninvasive tumor treatments owing to their high selectivity and efficiency. However, the harsh tumor microenvironment severely impairs their efficiency. Herein, the biodegradable Cu-doped zeolitic imidazolate framework-8 (ZIF-8) was synthesized for loading photosensitizer Chlorin e6 (Ce6) and CaO2 nanoparticles, followed by surface decoration by hyaluronic acid (HA), obtaining HA/CaO2-Ce6@Cu-ZIF nano platform. Once HA/CaO2-Ce6@Cu-ZIF targeting tumor sites, the degradation of Ce6 and CaO2 release from the HA/CaO2-Ce6@Cu-ZIF in response to the acid environment, at the same time, the Cu2+ active sites on Cu-ZIF was exposed. The released CaO2 decomposed to generate hydrogen peroxide (H2O2) and oxygen (O2), which alleviated the insufficiency of intracellular H2O2 and hypoxia in TME, effectively enhancing the production of hydroxyl radical (•OH) and singlet oxygen (1O2) in Cu2+-mediated chemodyanamic therapy (CDT) and Ce6-induced photodynamic therapy (PDT), respectively. Importantly, Ca2+ originating from CaO2 could further enhance oxidative stress and result in mitochondrial dysfunction induced by Ca2+ overloading. Thus, the H2O2/O2 self-supplying and Ca2+ overloading ZIF-based nanoplatform for cascade-amplified CDT/PDT synergistic strategy is promising for highly efficient anticancer therapy.